2004
DOI: 10.1099/jmm.0.45636-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic response of Helicobacter pylori to human plasma and bile

Abstract: To clarify further the role of chemotaxis in Helicobacter pylori colonization, the in vitro bacterium response to human plasma and bile (secretions containing chemoeffector compounds that are present in the gastric mucus layer) was examined. Human plasma, after dilution to 1 % (v/v) with buffer, was found to be a chemoattractant for the motile bacillus. Human gall-bladder bile, after dilution to 2 % (v/v) with buffer, was found to be a chemorepellent, but did not cause the motility of the bacillus to be dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…These findings do not exclude cheV2 and cheV3 in other specialized chemotactic responses. Several groups have reported chemotactic responses of H. pylori strains to bicarbonate, ammonia/urea, bile, and various amino acids (5,9,22,40). Yet, other studies have not been able to reproduce some of these findings (3), underscoring the need for more mechanistic studies of this system.…”
Section: Vol 188 2006mentioning
confidence: 80%
See 1 more Smart Citation
“…These findings do not exclude cheV2 and cheV3 in other specialized chemotactic responses. Several groups have reported chemotactic responses of H. pylori strains to bicarbonate, ammonia/urea, bile, and various amino acids (5,9,22,40). Yet, other studies have not been able to reproduce some of these findings (3), underscoring the need for more mechanistic studies of this system.…”
Section: Vol 188 2006mentioning
confidence: 80%
“…The H. pylori genome encodes three canonical membrane-spanning chemoreceptor proteins (TlpA, TlpB, and TlpC) and one soluble chemoreceptor protein (TlpD) (3,5,9,23,30). While several groups have demonstrated chemotactic responses to a variety of substrates including urea, bicarbonate, and amino acids (3,5,22,40), the substrate specificities of these chemoreceptors have not been determined.…”
mentioning
confidence: 99%
“…Serine has also been shown to behave as a chemoattractant for strains 26695 and 43504, and there is evidence that strain 26695 recognises arginine as a chemoattractant [30]. In contrast to the clinical isolates studied by Worku et al [29] , Cerda et al [30] have found no chemotactic response to alanine, histidine, or leucine in strains 26695 and 43504. Cysteine, glutamate, methionine and tryptophan also failed to elicit a chemotactic response.…”
Section: Discussionmentioning
confidence: 73%
“…Cysteine, glutamate, methionine and tryptophan also failed to elicit a chemotactic response. Furthermore, while Worku et al [29] found glutamic and aspartic acids to behave as weak chemorepellents, Cerda et al [30] reported that aspartic acid behaves as a chemoattractant of both H. pylori 26695 and 43504. Given the role of polar amino acids as chemotactic signals, it would be important to establish in the future if YckK plays a role in chemotaxis, and if so, which methyl-accepting chemotaxis protein it signals through.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation